The Neurobiology of Selenium: Looking Back and to the Future - Schweizer, Ulrich; Bohleber, Simon; Zhao, Wenchao; Fradejas-Villar, Noelia (Frontiers in Neuroscience, 2021)
Eighteen years ago, unexpected epileptic seizures in Selenop-deficient mice pointed to a potentially novel, possibly underestimated, and previously difficult to study role of selenium in the mammalian brain. This mouse model was the key to open the field of molecular mechanisms: delineate the roles of selenium and individual selenoproteins in the brain, and answer specific questions like: how does selenium enter the brain? which processes and which cell types are dependent on selenoproteins? What are the individual roles of selenoproteins in the brain? Many of these questions have been answered and much progress is being made to fill remaining gaps. Mouse and human genetics have together boosted the field tremendously, in addition to traditional biochemistry and cell biology. As always, new questions have become apparent or more pressing with solving older questions. We will briefly summarize what we know about selenoproteins in the human brain, glance over to the mouse as a useful model, and then discuss new questions and directions the field might take in the next eighteen years.